Impact of density and special features of manufacturing process on drying of autoclaved aerated concrete masonry blocks (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Autoclaved aerated concrete (AAC) masonry blocks are construction material with high heat insulation parameters. In time of sustainable construction, this material can be used as a load bearing construction material for a range of buildings where it is necessary to obtain high heat insulation parameters of external delimiting constructions. The main problem of autoclaved aerated masonry constructions is the significant influence of relative humidity rate and its gradient on heat resistivity properties of the masonry constructions. Therefore it is important to monitor the drying process of AAC masonry constructions in order to avoid the sealing of moisture inside the masonry by early application of finishing layers on the construction. As there is a variety of manufacturers who offer AAC masonry blocks and the manufacturing process of the blocks slightly differ as well as the ingredients used for the manufacturing of the blocks this research has been done to determine the impact of manufacturing features and density of the blocks on their drying properties. The testing has been performed by non-destructive testing method – electrical impedance spectrometry (EIS) In the paper, there are included results of research of correlation between EIS and moisture content rate in masonry blocks provided by different manufacturers. All used blocks are with similar material density. As a result of the research correlation formulas between saturation rate of the material and EIS measurement result have been established and a graph of humidity migration throughout the cross section of the masonry construction has been determined.